Eficiência ambiental da agricultura e a transição florestal no Cerrado brasileiro - Simões, Ricardo Muniz (Universidade Federal de São Carlos, 2025)
The Cerrado, one of the most biodiverse biomes on the planet, plays a crucial role in maintaining ecosystems and supporting Brazil’s agriculture. However, the continuous expansion of the agricultural frontier has accelerated deforestation, converting vast areas of native vegetation into pastures and croplands. This study analyzes environmental efficiency (EE) and technical efficiency (TE) in agriculture in municipalities of the Brazilian Cerrado in 2017, investigating their main determinants considering the forest transition theory. To achieve this goal, a stochastic production frontier was estimated using municipal data, with deforestation modeled as an environmentally detrimental input. The results indicate an average TE of 85%, while EE is lower, at 81%. A heterogeneous distribution of forest transition stages in the Cerrado was also observed: municipalities in the south are predominantly in the transition between the second and third phases, while the central and northeastern regions remain mostly in the initial stages, suggesting that deforestation in these areas may increase in the future. Among the efficiency determinants analyzed, no-till farming and technical assistance stand out due to their potential to reduce deforestation. Finally, the results highlight the urgency of public policies focused on conserving the Brazilian Cerrado, particularly the expansion of conservation and environmental protection areas.
Environmental efficiency of agriculture and the forest transition in the Brazilian Cerrado
Keywords: Cerrado; Eficiência ambiental; Eficiência técnica; Transição florestal; Agricultura; Environmental Efficiency; Technical Efficiency; Forest Transition; Agriculture; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA AGRARIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS